Lettres croisées de Jérôme et Augustin. Edited by Carole Fry - White, Carolinne (The journal of theological studies, 2010)
In the preface to this Latin–French bilingual edition of the sporadically intense correspondence between Jerome and Augustine over a period of some 25 years straddling the end of the fourth century, Carole Fry makes it clear that she intends not only to provide a French translation of the letters, to add to the English and German translations produced during the last 20 years by White, Hennings, and Fürst, but to focus not so much on the historical and theological aspects of the correspondence as on an investigation into linguistic areas that she believes will shed light on the authors’ ways of thinking and on their personalities.